Los puentes del río Virilla entre San José y Heredia (Costa Rica) - Artavia Rodríguez, Luís Guillermo (2016)
This article explores, from both a historical and a geographical perspective, a site of strategic importance for transport in the context of the central region of Costa Rica and its link to the Pacifc coast, during the frst half of the XIX Century. Specifcally studied is how over time and space, a geographical barrier formed by the Virilla river and the deep canyon it formed, was overcome bythe building of Bridges. A historical reconstruction is carried out of the process that resulted in the building of different bridges over a period of time, that facilitated the ﬂow of goods and the traffc of persons between the main cities within the central region and the port of Puntarenas, and of its tactical importance in the Guerra de la Liga (1835). Finally, some basic construction elements regarding the actual construction of the works are presented, and these are related to the existing structural remains of the stone bridge that was used between 1838 and 1929.